Riboflavin as migraine prophylaxis in adolescents - Athaillah Athaillah; Yazid Dimyati; Johannes H. Saing; Bistok Saing; Hakimi Hakimi; Aznan Lelo (Indonesian Pediatric Society, 2012)
Background Migraine is a cause of recurrent headaches inchildren. Riboflavin has been shoto be efficacious in preventingmigraine in adults. However, there has been little research on itsuse in children and adolescents.Objective To assess the effectiveness of riboflavin for migraineprevention in adolescents.Methods We conducted a randomized, doubleô€…blind, controlledtrial in the Islamic Centre of the Musthafav.iyah Mandailing NatalDistrict, North Sumatera, from May to July 2010. Adolescents lith migraines, as defined criteria, were included. Subjects were divided into two groups,receiving either 400 mg of riboflavin or placebo for 3 months.Headache frequency was measured in headache days per month,headache duration was measured in hours, and functionaldisability was measured using the Pediatric Migraine DisabilityAssessment Scale (PedMIDAS). Migraines were assessed before,during and after intervention. Student's tô€…test was used forstatistical analysis.Results A total of 98 patients, ranging from 12 to 19 years inage (mean age 14.0 years) were enrolled. We found a significantreduction in headache frequency in the second and third months.Headache duration also differed significantly third months (P=0.012 and P=O.OOl, respectively). Riboflavindecreased disability, as indicated by lower PedMIDAS scores inthe riboflavin group compared to the placebo group (26.1 and34.3, respectively, P= 0.001).Conclusion Riboflavin effectively decreased migraine frequency,duration and disability in adolescents. [Paediatr Indones.2012;52:132-7].